Development Of Line Width And Type Control Of 2d Cad Software Based On Iso Technical Drawing Standard - Nopnakorn, Pitoon (2003)
Engineering drawing is the media of communication in manufacturing process. In order to communicate in the same graphic language in engineering, the technical drawing standard has been specified by the International Organization for Standardization (ISO). Some commercial CAD softwares such as AutoCAD, AutoSketch and Solid Edge provided high-end ability to work whether in 3D or 2D space. Their width, length and proportion of printed lines conform to the ISO Technical Drawing Standard. But the procedures and interface to create line width and line type for simple drawing are sometime tedious and complex. The aim of this research work is to develop a 2D CAD software with emphasize on line width and line type control based on the ISO technical drawing standard for technical drawing.The ISO 128 part 20, 21 , and 24 are fundamental standard applied to the proposed software. The design of User Interface (VI) has been done in Windows XP operating system environment and Pascal-based Delphi 5 Standard as the visual programming tools. The format of drawing file was designed as the independent format, textual file, on the basis of Computer Graphics Metafile format (CGM) and Data Exchange File format (DXF). Seven drawing were printed in various line widths from 0.25 mm to 2.0 mm. Every drawing was proved the line width, length of line elements and continuous line are the same dimension as a manuscript drawing and specification in the ISO standard. The human-computer interfaces of the developed software were simplified for line width and line type control. The time taken to produce a technical drawing is less as compare to commercial softwares such as AutoCAD, AutoSketch and Solid Edge. Keystroke-level model was applied for this purpose.